The Long-Term Outcome in a Cohort of 52 Patients With Symptomatic Intramedullary Spinal Cavernous Hemangioma After Microsurgery and Emergency Rescue Surgery - Duan, Yu; Mao, Renling; Qin, Xuanfeng; Liao, Yujun; Li, Jian; Chen, Gong (Frontiers in Medicine, 2022)
Background：Surgery is the mainstay treatment for patients with symptomatic intramedullary spinal cavernous hemangioma (ISCH), however the time of surgical intervention remain controversial. In this study, we proposed the emergency rescue surgery (ERS) for deteriorative patients. The prognostic factors of patients with ISCH after microsurgery and the clinical effect of ERS were analyzed. Methods: From January 2013 to November 2019, 52 patients with symptomatic ISCH treating by microsurgical treatment were collected, ranging in age from 17 to 66 years old (mean: 45.8±13.5 years). The course of disease ranged from 2 days to 20 years. Of 52 lesions, 17 lesions were in cervical segment, 25 in thoracic segment and 10 in lumbosacral segment; and 7 cases were at ventral surface, 25 cases at dorsal surface, and 20 cases at central spinal cord. The sagittal diameter ranged from 1mm to 58mm (median: 17.3mm). The transverse diameter ratio ranged from 20% to 80% (median: 50.7%). Thirty-two patients were diagnosed as deteriorative type and 22 were treated by ERS. Results: At 12 months after surgery, all patients were follow-up, no residual or recurrence was found in all patients. 25 patients (48.1%) showed spinal cord functional improvement after surgery; 25 (48.1%) had no functional change; 2 (3.8%) got worse. For deteriorative patients, ERS group had significantly higher improvement rate than non-ERS group (2=5.393，P=0.02); For all 52 patients, The factors as Lesion at ventral surface (Z= 10.453, P = 0.015), or at lumbosacral segment ( 2=9.259, P=0.010) and longer course of disease (Z=-2.021, P=0.043) were potential risk in functional recovery in univariate analysis; and in multiple-factor analysis, the lesion at lumbosacral segment (OR=4.004, 95%CI: 1.341 11.961, P=0.013) was the independent risk factors for the functional recovery. Conclusions: Microsurgical resection is safe and effective for symptomatic ISCH. ERS is an effective way to improve deteriorative patients’ spinal cord function at long-term follow up. The lesion at lumbosacral segment is one of poor prognostic factors.